Complementary resources, entry mode and the performance of diversified subsidiaries: empirical research based on China National Tobacco Corporation - Li Jun (2018)
This dissertation explores the relationship between the complementary resources and entry mode in diversification transformation strategy of China National Tobacco Corporation adopting resource dependence theory and resource base theory. We use "multiple regression empirical analysis method" and "longitudinal case study" approach to test whether the complementary resources and entry mode are related to diversified subsidiary’s performance. We address two main research questions: a) how does diversified subsidiary’s dependence on the main business’ resources affect its performance? And b) whether do entry mode have influence on the relationship between the complementary resources and diversified subsidiary’s performance. We conduct an extensive literature review and proposed relevant theoretical hypotheses of the relationship among the complementary resources, entry mode, and diversified subsidiary’s performance. We survey on resource complementarity, entry mode and performance based on questionnaire distributed to the top management in both CNTC and its subsidiaries and verify our hypotheses using raw date from 196 valid questionnaires. It is found that remarkable positive relation is only found between resource complementarity and diversified subsidiary’s financial performance, and diversified entry modes exert a moderating effect on resource complementarity’s relations with diversified subsidiary’s performance, financial performance and growth performance. Further, we explore the evolving relationship of the resource dependency and entry mode in the corporation’s diversification in a dynamic perspective based on a longitudinal case drawing on a rich array of documents from CNTC’s progressing in strategic transformation. Our findings have practical significance in the design of a gradual diversification transformation strategy, and especially to managers of CNTC which diversification has become an inevitable choice due to increasingly tight smoke-free policy.